Determinan Pendapatan Usaha Pedagang Pakaian Di Kabupaten Mimika (Studi Kasus Pedagang Pakaian Pasar Sentral) - Yamin Muhammad; Rosdiana Rosdiana (JURNAL KRITIS (Kebijakan, Riset, dan Inovasi), 2023)
This research aims to determine the effect of inventory and plans for providing goods on the income of clothing traders at Timika Central Market; the approach taken in this research is a quantitative approach; collecting data through questionnaires then tabulating and testing to determine the effect of inventory and plans for providing goods on the income of clothing traders at Timika Central Market; based on the results of the analysis in this study, it shows that inventory (X1) partially influences income with the test results obtaining a value of 0.001 < 0.05 and a t value of 3.411 > t table 1.998 and the plan to supply goods (X2) partially influences the income of clothing traders at the Timika Central Market with test results 0.001 < 0.05 and tcount value 3.362 > ttable 1.998;